198k views
3 votes
Y=-2x - 7
4y - 3x = 16

Y=-2x - 7 4y - 3x = 16-example-1
User Twilbrand
by
6.6k points

2 Answers

3 votes

Answer:

x=−4 and y=1

Explanation:

Rewrite equations:

y=−2x−7;−3x+4y=16

Step: Solvey=−2x−7for y:

y=−2x−7

Step: Substitute−2x−7foryin−3x+4y=16:

−3x+4y=16

−3x+4(−2x−7)=16

−11x−28=16(Simplify both sides of the equation)

−11x−28+28=16+28(Add 28 to both sides)

−11x=44

-11x/-11=44/-11

x=−4

Step: Substitute−4forxiny=−2x−7:

y=−2x−7

y=(−2)(−4)−7

y=1(Simplify both sides of the equation)

x=−4 and y=1

User EyalG
by
6.0k points
4 votes

Answer:

Explanation:

Y=-2x - 7 4y - 3x = 16-example-1
Y=-2x - 7 4y - 3x = 16-example-2
User Geoffrey De Smet
by
5.6k points